The challenges of governance in a complex world - Ho, Peter 1968- (World Scientific Publishing Co., 2018)
The Challenges of Governance in a Complex World collects the four IPS-Nathan Lectures that Mr Peter Ho, the Institute of Policy Studies’ third S R Nathan Fellow for the Study of Singapore delivered between April and May 2017, and includes highlights of his dialogue with the audience.